Kompetensi kepribadian guru PAI menurut kitab Adabul Alim Wa Muta’alim KH. Hasyim Asy’ari - Anwar, Agus Khoirul; Supraha, Wido; Sastra, Ahmad (Tawazun: Jurnal Pendidikan Islam, 2024)
Education in Islam aims to build a perfect person, as exemplified by the Prophet Muhammad SAW, not just to produce good workers or citizens. The figure of an ideal Islamic Religious Education (PAI) teacher is key in building a generation with character. However, currently many PAI teachers lack exemplary behavior, such as playing games while teaching or joking when students are praying. This study aims to explore the concept of teacher personality competence according to KH. Hasyim Asy'ari in the book Adabul Alim wa Muta'alim as an ideal model that can be applied in the formation of PAI teacher personality. This research method uses a qualitative approach through text study and descriptive analysis. The results showed that the concept of personality competence in the book emphasizes trustworthiness, noble character, and exemplary. In conclusion, the application of this concept is relevant to forming a good PAI teacher personality and producing a golden generation with character and noble character. Keywords: Adabul Alim wa Muta'alim; Hasyim Asy'ari; Islamic Religion Teacher; Personality Competence. Abstrak Pendidikan dalam Islam bertujuan membangun insan yang sempurna, sebagaimana dicontohkan Nabi Muhammad SAW, bukan sekadar menghasilkan pekerja atau warga negara yang baik. Sosok guru Pendidikan Agama Islam (PAI) ideal menjadi kunci dalam membangun generasi berkarakter. Namun, saat ini banyak guru PAI yang kurang menunjukkan keteladanan, seperti bermain game saat mengajar atau bercanda saat siswa berzikir. Penelitian ini bertujuan mengeksplorasi konsep kompetensi kepribadian guru menurut KH. Hasyim Asy’ari dalam kitab Adabul Alim wa Muta’alim sebagai model ideal yang dapat diterapkan dalam pembentukan kepribadian guru PAI. Metode penelitian ini menggunakan pendekatan kualitatif melalui kajian teks dan analisis deskriptif. Hasil penelitian menunjukkan bahwa konsep kompetensi kepribadian dalam kitab tersebut menekankan sifat amanah, akhlak mulia, dan keteladanan. Kesimpulannya, penerapan konsep ini relevan untuk membentuk pribadi guru PAI yang baik dan menghasilkan generasi emas berkarakter serta berakhlak mulia.